(untitled) (One Health Journal of Nepal, 2022)
Introduction: Issues with oral and dental health rank high on the list of concerns and complaints expressed by the elderly. The purpose of this study was to determine oral health-related quality of life (OHRQoL) among elderly people from Mohnyin, Myanmar. Methods: We conducted a community based cross-sectional study among 312 elderly people of Mohnyin, Myanmar. Ethical approval was obtained. We conveniently recruited the participants in the study. General characteristics, dental status and denture status were obtained from all the participants. We used Geriatric Oral Health Assessment Index (GOHAI) to assess oral health-related quality of life (OHRQoL). Data was entered in EpiData and transported to SPSS version 18 for further analysis. Results: Of the total, 46.1% had a high GOHAI score, whereas 53.8% had a low GOHAI score. The mean score of GOHAI was 41.18±5.7 (mean±SD). About 56.1% of the elderly had at least 20 remaining natural teeth and the prevalence of wearing dentures was only 19.9%. Conclusions: This study’s results support the implementation of preventative and restorative public health policies aimed at enhancing oral health care and education for the elderly.